Approaches for University Students and their Relationship to Academic Performance - Evelyn Fernández-Castillo; Zaida Irene Nieves-Achón (Universidad Nacional, Costa Rica, 2015)
The way students perceive learning is influenced by multiple factors. The present study aimed at establishing relationships between the learning approaches, academic performance, and the academic year in a sample of students from different courses of Universidad Central  "Marta Abreu", Las Villas. For this ex post facto study, a probabilistic sample was used based on a simple random sampling of 524 university students who participated in the Study Process Questionnaire.  The analysis of variance (MANOVA and ANOVA) and the analysis of clusters reported associations between a deep approach to learning and a better academic performance.  These analyses showed differences in the learning approach in the different courses, predominantly a soft approach.